Workshop Advokasi Hukum dan Kebijakan Publik bagi Pimpinan Cabang Ikatan Mahasiswa Muhammadiyah Bantul - Mukhtar Mukhtar; Tanto Lailam (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The workshop on legal advocacy and public policy for the Lembaga Advokasi dan Kajian Hukum Pimpinan Cabang Ikatan Mahasiswa Muhammadiyah Bantul is an activity of the Muhammadiyah Association-Based Community Service Program (PPM-Muhammadiyah) with the title Empowering Muhammadiyah Young Cadres in Legal Advocacy and Public Policy. This workshop was conducted to answer and provide solutions to the weaknesses of the cadres of LAKH PC IMM Bantul, namely: the lack of understanding of legal cases and public policies, lack of ability to carry out legal strategies and advocacy efforts on legal and public policy problems that occur in the community, as well as the lack of legal advocacy and public policy actions. This workshop focused on explaining the basics of advocacy, functions of advocacy, targets of advocacy, steps and schemes of advocacy on case law and public policy, strategies of advocacy, and requirements for someone to advocate for law and public policy. On the other hand, it also describes the constitutional rights of citizens and the problems of rules and regulations and public policies in Indonesia, especially local laws and regulations. The Legal and policy advocacy focused on advocacy (procedural law) in judicial institutions (district courts, Supreme Court, Constitutional Court, and others are also comprehensively presented. The most exciting thing is that the exposure to various legal cases and public policies and their advocacy approach has provided a strong understanding for the participants.